2015
DOI: 10.3390/molecules200814377
|View full text |Cite
|
Sign up to set email alerts
|

Pheonolic Compounds from the Fruits of Viburnum sargentii Koehne

Abstract: Seven phenolic compounds were isolated from the fruits of Viburnum sargentii Koehne by silica gel column chromatography and preparative HPLC. On the grounds of chemical and spectroscopic methods, their structures were identified as (−)-Epicatechin (1),, quercetin-3-O-rutinoside (7). Compounds 5 and 6 are new monoterpene phenolic glycosides, compounds 1, 3 and 4 were isolated from the Viburnum genus for the first time, and compounds 2 and 7 from the Viburnum sargentii Koehne for the first time. Compounds 1-7 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…polyphenolic contents have been analyzed in berries of other species of Viburnum including V. dilatatum, V. opulus, and V. sargentii. [27,32,[44][45][46][47] Kim et al [32] reported phenolic composition of squeezed fruit juice extracts of Viburnum dilatatum by employing NMR and liquid chromatography/MS techniques. The phenolic compounds included cyanidin 3-sambubioside, cyanidin 3-glucoside, 5-O-caffeoyl-4-methoxyl quinic acid, quercetin, and chlorogenic acid.…”
Section: Polyphenolic Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…polyphenolic contents have been analyzed in berries of other species of Viburnum including V. dilatatum, V. opulus, and V. sargentii. [27,32,[44][45][46][47] Kim et al [32] reported phenolic composition of squeezed fruit juice extracts of Viburnum dilatatum by employing NMR and liquid chromatography/MS techniques. The phenolic compounds included cyanidin 3-sambubioside, cyanidin 3-glucoside, 5-O-caffeoyl-4-methoxyl quinic acid, quercetin, and chlorogenic acid.…”
Section: Polyphenolic Compositionmentioning
confidence: 99%
“…Kraujalyte et al [27] reported presence of nine phenolic compounds (chlorogenic acid, neochlorogenic acid, quinic acid, catechin, epicatechin, procyanidin C1, and three other unidentified compounds) in V. opulus juice by using ultra high performance liquid chromatography coupled to quadruple and time-of-flight mass spectrometry (UPLC-QTOF-MS). Xie et al [47] isolated seven phenolic compounds from the fruits of…”
Section: Polyphenolic Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The five known compounds were identified as 5,7,4′-trihydroxyflavone 6-C- [14], quercetin 3-O-rutinoside (3) [15], 5,7,4′-trihy …”
Section: Resultsmentioning
confidence: 99%
“…The five known compounds were identified as 5,7, [14], quercetin 3-O-rutinoside (3) [15], 5,7,4 1 -trihy droxyflavone 6-C-β-D -glucopyranoside (4) [16], and 3 1 -methoxy-5,7,4 1 -trihydroxyflavone 6-C-β-D-glucopyranoside (5) [17], by comparison of various data with the reported compounds. , and 113.6 (CH) were deduced to arise from a trans-caffeoyl moiety based on the analysis of 1 H-1 H COSY, HMQC, and HMBC of 6 and the comparison of 1 H-and 13 C-NMR spectra of 6 with the reported values [18].…”
Section: Resultsmentioning
confidence: 99%